NEW GUIDELINES FOR THE MANAGEMENT OF RHEUMATOID ARTHRITIS (EULAR, 2013): THE PLACE OF GLUCOCORTICOIDS - E. L. Nasonov (Научно-практическая ревматология, 2016)
Despite major advances in the management of rheumatoid arthritis (RA), whicare associated with the development of new methods for its early diagnosis, the clinical introduction of a wide range of innovative medications and particularly the improvement of a strategy for their use, glucocorticoids (GC) still remain the most important  component of pharmacotherapy for this disease in real clinical practice. This publication that is a continuation of a series of papers devoted to the discussion of the main points of the 2013 European League against Rheumatism (EULAR) guidelines for the treatment of early RA, deals with the place of GC. An analysis of available data suggests that GC should be reserved for patients showing a high activity of the inflammatory process and having factors associated with a poor prognosis, but also, in the absence of risk factors for adverse events (AE), of course, contraindications to GC therapy. Throughout the use of GC, their AE should be meticulously monitored in compliance with the EULAR guidelines. It is anticipated that the wider use of combined therapy with methotrexate and a GC in earlyRA will be able to improve its prognosis in at least some patients and to cause a substantial decrease in the burden of disease, by reducing the risk of disability and the needs for expensive biological agents and joint replacement. All this confirms that it is relevant to include the proposition for using GC into the 2014 Guidelines for the management of rheumatoid arthritis of the All-Russian public organization “Association of Rheumatologists of Russia”.